2021
DOI: 10.48550/arxiv.2103.05398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

All-optical input-agnostic polarization transformer via experimental Kraus-map control

Abstract: The polarization of light is utilized in many technologies throughout science and engineering. The ability to transform one state of polarization to another is a key enabling technology. Common polarization transformers are simple polarizers and polarization rotators. Simple polarizers change the intensity depending on the input state and can only output a fixed polarized state, while polarization rotators rotates the input Stokes vector in the 3D Stokes space. We demonstrate an all-optical input-agnostic pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…We also confirm this via simulations in Appendix A. This would suggest that the polarization of light could serve as a useful degree of freedom in FSO communications, particularly given that polarization transformers have been shown to be able to manipulate the state and degree of polarization (SOP and DOP, respectively) [21] in ways that may be suitable for FSO communications [22]. It has also been shown that polarization can be used to encode and transmit information securely [23], and that states with a DOP of 1 are preserved in the presence of turbulence [16,24].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…We also confirm this via simulations in Appendix A. This would suggest that the polarization of light could serve as a useful degree of freedom in FSO communications, particularly given that polarization transformers have been shown to be able to manipulate the state and degree of polarization (SOP and DOP, respectively) [21] in ways that may be suitable for FSO communications [22]. It has also been shown that polarization can be used to encode and transmit information securely [23], and that states with a DOP of 1 are preserved in the presence of turbulence [16,24].…”
Section: Introductionsupporting
confidence: 66%
“…The desired partially polarized states are generated by a Mach-Zehnder interferometer, where a polarizing beamsplitter generates beams of horizontal and vertical polarizations, which are then recombined on a 50:50 non-polarizing beamsplitter (BS), such that they are separated by a small distance and not coaxially superposing. This allows for control over the DOP by adjusting relative intensity of each arm of the interferometer [21,32]. This is done by attenuating one arm by tuning a variable neutral-density filter.…”
Section: Methodsmentioning
confidence: 99%
“…As with all paradoxes in the technical sense of the word, a resolution awaits. The creation of such an input-agnostic polarization transformer from linear optical devices requires postselection to enable a lossless polarizer (Zhang et al, 2021); in actuality, some light is always lost by such a polarizer. Such a transformation with Kraus operators enacting Eq.…”
Section: Speculative Constraints On Polarization Changesmentioning
confidence: 99%
“…Quantum polarization has been used for quantum key distribution (Bennett et al, 1992;Muller et al, 1993), Einstein-Podolsky-Rosen tests (Kwiat et al, 1995), quantum teleportation (Bouwmeester et al, 1997), quantum tomography (James et al, 2001), weak value amplification (Hallaji et al, 2017), and more. However, the study of the changes in quantum polarization have not, to our knowledge, been the focus of any major review, which is a void that must especially be filled due to the proliferation of recent experiments on polarimetry with explicitly quantum mechanical states of light (Altepeter et al, 2011;Bogdanov et al, 2004;Daryanoosh et al, 2018;Graham et al, 2006;Mitchell et al, 2004;Oza et al, 2010;Rosskopf et al, 2020;Slussarenko et al, 2017;Sun et al, 2020;Toussaint et al, 2004;Yoon et al, 2020;Zhang et al, 2021). We set forth to present a complete picture of quantum polarimetry in this work.…”
Section: Introductionmentioning
confidence: 99%